Oorreding in evangelisasie - Merwe, P. J. van der (Hervormde teologiese studies, 1994)
Persuasion in evangelism Is persuasion as researched and applied in the different secular fields relevant to evangelism? To many evangelists this is hardly a question to consider, since they take a positive answer as self evident. It is a different matter however when faith in Jesus Christ is marketed as a means to heavenly retirement, or when the fears and emotions of persons are manipulated in order to pressure- sell the gospel. This article looks at two examples of applied persuasion, i e in marketing, and in training and management. One of the aims of evangelism, conversion, is also considered. It is found that many of the principles and techniques of persuasion as formulated may indeed be used in influencing and persuading nonbelievers on condition that specific principles be honoured. The article aims at addressing four principles in this regard.